THE INFLUENCE OF JOB EXPECTATION, JOB SATISFACTION, AND GOVERNMENT POLICY TOWARDS THE WORK STRESS, JOB ENTHUSIASM AND CONTINUANCE COMMITMENT OF THE HONORARIUM TEACHER - Tuty Sariwulan; Iskandar Agung; Unggul Sudrajat; Genardi Atmadiredja (Jurnal Cakrawala Pendidikan, 2019)
This study aims to determine the effect of job expectations (JE), job satisfaction (JS), and government policy (PG) on work stress (WS), work passion (JEn), and continuance commitment (CC) to honorarium teachers in middle and high school. Data collection was done through questionnaires and analyzed using the SEM approach with the help of the Lisrel 8.80 program. The results of the analysis show that the variables JE, JS, and PG have an influence on WS; and WS has an influence on JEn and CC. Explicitly, the conditions and situations faced by honorary teachers tend to create a desire to find new workplaces. This was also reinforced by the issuance of Government Regulation No. 49/2019 concerning the acceptance of workers with work agreements and prohibits the existence of honorarium status. It is recommended, it is necessary to give priority to honorary teachers by not using work contracts, but by treating them for a certain period of time, then being appointed as permanent (non-ASN) teachers if they are judged to meet their requirements and eligibility.